Upaya Peningkatan Personal Branding Bagi Anggota Tiara Kusuma DPC Kota Semarang - Nurulisma Saputri; Kuswidyaningrum N.J (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Tiara Kusuma is the Indonesian Association of Estheticians and Salon Entrepreneurs as well as a forum for Indonesian Estheticians and Salon Entrepreneurs. Its members are spread throughout Indonesia and have branches in each region. Tiara kusuma DPC Semarang city is a gathering place for beauticians. In routine events, activities not only gather but also share knowledge with each other. Work in the field of beauty is in great demand, especially as a makeup artist. Personal branding is a knowledge that a makeup artist needs to know to form his own product image. One of the media for effective personal branding is social media. Social media can further develop our products to be better known and attractive in the wider community. So that it can increase the selling value of the business. AKS Ibu Kartini Semarang provides knowledge about personal branding. A community service was held for Efforts to Improve Personal Branding for Tiara Kusuma DPC Members of Semarang City. The knowledge provided by members is personal branding through social media. The purpose of this service is that Tiara Kusuma members can make their product image better so that they can attract and increase their selling value and income. There are several stages in the implementation of the activity, including the preparation stage, the implementation stage, the question and answer and the closing. The activity was carried out in the form of lectures, presentations and questions and answers which were attended by 30 members of Tiara Kusuma DPC Semarang City. The material presented was in the form of personal branding through social media. The activity went smoothly, the participants increased their knowledge related to personal branding.